2021
DOI: 10.1021/acssuschemeng.1c01065
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Supports Activated with Divinyl Sulfone in Enzyme Coimmobilization: Possibility of Multipoint Covalent Immobilization of the Most Stable Enzyme and Immobilization via Ion Exchange of the Least Stable Enzyme

Abstract: Vinyl sulfone (VS)–agarose beads were used to develop a new strategy to coimmobilize enzymes with very different stabilities, enabling the reuse of the most stable immobilized enzyme. Two model combi-biocatalysts were prepared. First, trypsin and chymotrypsin were multipoint covalently coimmobilized on VS–agarose, the support was blocked with ethylenediamine, and then β-galactosidase from Aspergillus oryzae was coimmobilized via anion exchange. Both immobilized proteases were more stable than the immobilized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…120 Here, the development of new enzyme immobilization strategies to solve the problem of poorly matched enzyme stability plays a special role and is an area of particular growth. [136][137][138][139][140] Enzyme immobilization may also be coupled to other techniques to improve enzyme features, such as site-directed mutagenesis, directed evolution or chemical modification. 10,109,[141][142][143][144] In fact, of special interest are those strategies where site-directed mutagenesis or chemical modification has been developed to improve enzyme immobilization itself.…”
Section: Roberto Fernandez-lafuentementioning
confidence: 99%
See 3 more Smart Citations
“…120 Here, the development of new enzyme immobilization strategies to solve the problem of poorly matched enzyme stability plays a special role and is an area of particular growth. [136][137][138][139][140] Enzyme immobilization may also be coupled to other techniques to improve enzyme features, such as site-directed mutagenesis, directed evolution or chemical modification. 10,109,[141][142][143][144] In fact, of special interest are those strategies where site-directed mutagenesis or chemical modification has been developed to improve enzyme immobilization itself.…”
Section: Roberto Fernandez-lafuentementioning
confidence: 99%
“…For example, it has been shown that this blocking step may be used to perform the co-immobilization of several enzymes, enabling the reuse of the most stable enzyme after the inactivation of the least stable. 137,139 4.10. Immobilization protocols are not finished when all the enzyme activity is incorporated in the support Capitalizing on enzyme immobilization to the full, it is not only necessary to utilize a suitable support, an adequate degree of activation of the support and a convenient reactive group on the support.…”
Section: No Use Of Enzyme-support Interaction End Point Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic processes have been widely used due to the advantages of fast speed, strong specificity, green environmental protection, and saving reagents and energy. [1][2][3][4][5][6] The designed enzyme-catalyzed chemical reactions have high selectivity and efficiency in saving energy. As a green catalyst, such as other enzymes, Candida antarctica lipase B (CALB, 3.1.1.3) has advantages when used as a catalyst, such as mild reaction conditions, chemo-and enantioselectivity, and high catalytic activity under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%